The Development of Tahfiz Quran Movement in the Reform Era in Indonesia - Sofyan, Muhammad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
This paper is aimed to explore the development of Tahfiz Quran movement in the reform era in Indonesia, especially the developments emerging from 2005 until now. To view these developments, the writer will highlight the DÂ±rul Quran institutions, ODOJ community (One Day One Juz), and methods of al-Qosimi and Yadain.by using obsrvation and documentery study. The study found that institutions, programs and methods of Tahfiz in that era had become transformative Tahfizul Quran, with modern institutional system, flexible program to reach almost all level of society, innovative and creative learning methods in accordance with the demand of todays improvement. However, these developments do not eliminate the fundamental things that have been built by the scholars of Tahfiz previously.